2014
DOI: 10.1364/oe.22.013804
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-long high-sensitivity Φ-OTDR for high spatial resolution intrusion detection of pipelines

Abstract: An ultra-long phase-sensitive optical time domain reflectometry (Φ-OTDR) that can achieve high-sensitivity intrusion detection over 131.5km fiber with high spatial resolution of 8m is presented, which is the longest Φ-OTDR reported to date, to the best of our knowledge. It is found that the combination of distributed Raman amplification with heterodyne detection can extend the sensing distance and enhances the sensitivity substantially, leading to the realization of ultra-long Φ-OTDR with high sensitivity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
117
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 355 publications
(136 citation statements)
references
References 8 publications
0
117
1
3
Order By: Relevance
“…5. It can be found that the power of the RS signal over the whole 49 km keeps relatively even by optimizing the power of pulse light and forward Raman pump [4], and the power difference of the fitting curve between the strongest and the weakest positions is less than 3 dB. To verify the vibration performance of this hybrid system, vibration measurement at the end of fiber is employed.…”
Section: Vibration Testmentioning
confidence: 99%
See 1 more Smart Citation
“…5. It can be found that the power of the RS signal over the whole 49 km keeps relatively even by optimizing the power of pulse light and forward Raman pump [4], and the power difference of the fitting curve between the strongest and the weakest positions is less than 3 dB. To verify the vibration performance of this hybrid system, vibration measurement at the end of fiber is employed.…”
Section: Vibration Testmentioning
confidence: 99%
“…The main nonlinear effect has been demonstrated to be modulation instability, which comes earlier than stimulated Brillouin scattering (BS) with the growing of the launching power of the probe pulse [3]. But BS still has to be considered even the stimulated BS does not occur, especially when the direct detection is employed (the spontaneous BS and RS are detected simultaneously) [4]. As to other aspect, in many applications, like structure health monitoring (SHM), after the vibration or acoustic wave generated by the structure transforming, the static strain (<0.1 Hz) of the structure usually changes accordingly.…”
Section: Introductionmentioning
confidence: 99%
“…Distributed fiber optic sensors are widely used for variety of applications such as structural health monitoring, perimeter and pipeline security, temperature, pressure, strain, and vibration measurements due to its lightweight, ease of installation, and immunity to electromagnetic fields [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. One of the modern forward-looking fiber optic techniques, the so-called phase-sensitive optical time-domain reflectometry (w-OTDR), enables detection of acoustical perturbations along sensing optical fibers of several kilometers length [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the Φ-OTDR was successfully detection scheme [6,7]. The long-range Φ-OTDR for intrusion sensing is demonstrated with the assistance of Raman amplification [8]. The Φ-OTDR was also demonstrated for vibration sensing by adopting heterodyne coherent detection [9].…”
Section: Introductionmentioning
confidence: 99%